Komunikasi dan Resolusi Konflik Politik Partai Keadilan Sejahtera dalam Menangani Kasus Fahri Hamzah - Anna Kurniawati (Neolectura, 2021)
This study aims to determine the conflict resolution carried out by the Prosperous Justice Party in handling Fahri Hamzah’s case. This study uses organizational control theory. This study uses a qualitative methodology with literature review studies. Based on orgatizational control theory, PKS uses the method of domination:suppressive violence. PKS decision to dismiss Fahri Hamzah is a method of domination or suppression. Organizational Control Theory is a theory that regulates the ways of communication that are able to control employess. Organizational control is carried out in four ways: First, simple control or the uses of power that is on going and open. Second, technical control or use of technology tools. Third, bureaucracy, which is the use of organizational procedures and formal rules, as described by Weber. Employees are provided with a guidebook that include policies to follow, memos, repost reviews, meeting reviews and performance reviews which are used to convey other expectations. Fourth, concertive control. There are several methods used in conflict resolution: First, conflict stimulation methods, conflict reduction and conflict resolution. Second, the conflict reduction method is used to reduse the hostility caused by conflict. Third, conflict resolution methods, which are carried out through domination or supression, compromise, and integrarive problem solving. This study uses a qualitative methodology with a literature review study. Based on orgnizational control theory, PKS uses the method of domination or suppresive ciolence. The PKS decision to dismiss Fahri Hamzah is a method of domination or suppression.